PENGARUH PROGRAM TAHFIDZ TERHADAP SIKAP TAWADHU SANTRI DI PESANTREN QUR’AN AL-HIKMAH KEMANG BOGOR - Robi Putra; Ali Hadiyanto; Suyud Arif (KOLONI, 2022)
Memorizing the Qur'an is a very commendable and noble act. People who study, read or memorize the Qur'an are the chosen people who were chosen by Allah to receive the inheritance of the holy book of the Qur'an. Pesantren as an institution that is trusted by the community with prestige moral teaching, is actually able to survive in producing superior generations who have good morals and are capable in various fields. People who have a humble nature will admit mistakes and feel their knowledge is still lacking so they are open to receiving new ideas and wise advice from others. This trait is important for those who memorize the Qur'an. This study aims to determine how the effect of the implementation of the tahfidz program on the tawadhu attitude of students at the Al-Hikmah Islamic Boarding School Kemang Bogor. This research methodology uses a correlational quantitative approach, because this study aims to obtain answers to specific statements. Data collection techniques were carried out by filling out questionnaires, interviews and documentation. From the results of the research that the author has done, the tahfidz program variable has an influence on the attitude of tawadhu. The results of the linearity test showed that there was no significant linear relationship between the tahfidz program variable and the tawadhu attitude variable. While the correlation value of the influence of the tahfidz program on the tawadhu attitude of the santri at the Al-Hikmah Islamic Boarding School Kemang Bogor is 47.38%, which means that there is a moderate correlation between the tahfidz program variable and the tawadhu attitude variable. So, the effect of the tahfidz program on the attitude of tawadhu of students at Pesantren Al-Hikmah Kemang Bogor is only 21.39%, and 78.61% is influenced by other factors. Keywords: Tahfidz Program, Islamic Boarding School and Tawadhu Attitude